STRATEGI KAMPANYE POLITIK PRABOWO-HATTADAN PERANG PENCITRAAN DI MEDIA MASSA DALAM PEMILU PRESIDEN 2014 - Hidayanti Herpamudji, Dini (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
The President is a people’s choice. Choose the president is our right as citizens of Republic Indonesia. However,what if there are only two candidate and bothare equally good or equally bad? Each candidate need apolitical campaign strategies to created a better image than its competitor. At September 2013, elektability Jokowi - JK much higher than Prabowo- Hatta. The difference between the candidates reached 38 percent base on LSI Survey. Jokowi will win even nominated withanyone. This is similar with the 2009 elections, anyone vice SBY, he would still be elected president with just one round. How political campaign strategies of Prabowo-Hatta can rise elektabilitycloser to Jokowi-JK.Now the latest LSI survey, June 2014, after the establishment of the candidates and the start of the presidential campaign, the difference between the candidates is only 6 percent (Jokowi 45.0 percent vs. 38.7 percent Prabowo). Truly remarkable leap elektabilitas to Prabowo-Hatta although ultimately still could not win the presidential election in 2014. Keywords : politics campaign, 2014 Precidential election, cadidate image